2019
DOI: 10.1016/j.artd.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage bilateral distal femur replacement for traumatic distal femur fractures

Abstract: Treatment of periprosthetic distal femur fractures and comminuted intraarticular distal femur fractures with previous arthritis remains a difficult challenge for orthopedic surgeons. Previous case series have shown that distal femur replacement (DFR) can effectively compensate for bone loss, relieve knee pain, and allow for early ambulation in both of these fracture patterns. Owing to the typical low-energy mechanism of these injuries, a bilateral injury treated with DFR is rarely encountered. We present a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Twenty (66.7%) patients did not need home care, 5 (16.7%) received home care every day, and 5 (16.7%) received home care 1-2 times over two weeks. Mobility aids were used by 18 patients (60%) in the form of canes (9), walkers (8), and wheelchairs (1) (Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty (66.7%) patients did not need home care, 5 (16.7%) received home care every day, and 5 (16.7%) received home care 1-2 times over two weeks. Mobility aids were used by 18 patients (60%) in the form of canes (9), walkers (8), and wheelchairs (1) (Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Distal femoral resection knee arthroplasty may be a viable option for several non-oncologic indications [3,4], but the patients requiring this type of surgery are often elderly and with high medical comorbidity. Only limited data exist on the outcome of distal femoral resection knee arthroplasty for non-oncologic indications, but most of the recently published case series suggest it may be a reasonable treatment option [5,6,7,8,9,10]. The procedure appears to be a relatively safe option in terms of surgical complications and mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the case reported by Calmet et al [5], internal fixation using 4 cancellous lag screws was performed due to the fracture being open and associated with extensive soft tissue injury. Other treatments of supracondylar distal femur fracture include flexible intramedullary nails [11], plate fixation [12] using condylar plates, locking plates or blade plates [4], buttress plates with screws, total knee arthroplasty which is attempted in osteoporotic patients with severe comminuted fracture or preexisting arthritis [4] and distal femur replacement in patients with a previous total knee replacement [13]. The selection of the definitive fixation is based on the patient's status and the characteristics of the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Neal DC et al [7] reported their experience of a case of traumatic left open periprosthetic distal femur fracture with right closed intraarticular distal femur fracture with end stage arthrosis treated with single staged distal femur replacement, they concluded that single stage distal femur replacement provides the benefits of early mobilization and accelerated recovery in intraarticular distal femur and periprosthetic fractures.…”
Section: Discussionmentioning
confidence: 99%